Promoting Research Use Among Undergraduate Students Through Service Learning - Laura Dreuth; Martha Dreuth-Fewell (Networks: An Online Journal for Teacher Research, 2001)
In this article, we, the authors, examine a model of service learning for pre-service counselors enrolled in a research methods class. In a review of the counseling and human services literature, we found many references to teaching research methods; only a few articles, however, demonstrated using service learning in counselor or human services education. The students in this project joined a public health department, eight rural elementary schools, and university-based researchers to study bullying and school safety. The undergraduate students supported this project by conducting behavioral observations and informal interviews in the local schools. Positive responses were received from undergraduate students who responded to an open-ended follow-up questionnaire after they completed this course.